2021
DOI: 10.3389/fimmu.2021.800723
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose SARS-CoV-2 Replicon RNA Vaccine Induces Cellular and Humoral Immune Responses in Simian Immunodeficiency Virus Infected and Uninfected Pigtail Macaques

Abstract: The ongoing COVID-19 vaccine rollout is critical for reducing SARS-CoV-2 infections, hospitalizations, and deaths worldwide. Unfortunately, massive disparities exist in getting vaccines to vulnerable populations, including people living with HIV. Preliminary studies indicate that COVID-19 mRNA vaccines are safe and immunogenic in people living with HIV that are virally suppressed with potent antiretroviral therapy but may be less efficacious in immunocompromised individuals. This raises the concern that COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…First reports showed that most PLWH responded to mRNA vaccination in terms of binding and neutralizing Ab (82). This was consistent with observations made in a simian animal model (83). However, two recent reports stressed that patients with advanced HIV infection had lower response to mRNA vaccination (15,84).…”
Section: People Living With Hiv (Plwh)supporting
confidence: 77%
“…First reports showed that most PLWH responded to mRNA vaccination in terms of binding and neutralizing Ab (82). This was consistent with observations made in a simian animal model (83). However, two recent reports stressed that patients with advanced HIV infection had lower response to mRNA vaccination (15,84).…”
Section: People Living With Hiv (Plwh)supporting
confidence: 77%
“…In addition, this vaccine was evaluated in a proof-of-concept study using simian immunodeficiency virus (SIV)-infected pigtail macaques. A single dose of the vaccine was able to trigger humoral responses against the S protein in some animals, with a slightly better induction of nAbs in those receiving the highest dose (25 µg) compared to the lowest dose (5 µg) [ 49 ]. Although cellular responses were modest, this pilot study suggests that saRNA vaccines could be employed successfully in HIV-infected and other immunocompromised individuals, a particularly vulnerable population where the efficacy of approved SARS-CoV-2 mRNA vaccines has been reported to be lower [ 50 , 51 , 52 ].…”
Section: Delivery Strategies For Sarna Vaccines Against Sars-cov-2mentioning
confidence: 99%